Effect Of Modernization On Cooperative Performance in Medan City - Siregar, Nelda Fitry; Purwoko, Agus; Andayani, Lita Sri (Journal of Environmental and Development Studies, 2022)
This research aims to analyze the influence of modernization (with criteria: institutional pillar, business pillar and financial pillar) simultaneously on cooperative performance in Medan City. This study sample was 62 cooperative managers built by the Medan City Government who were active and NIK certified. This research was quantitative. The results of multiple linear regression analysis obtained a simultaneous coefficient of determination (RÂ²) of 0.615 where the value describes 61.5% of cooperative performance can be explained by institutional pillar variables (X1), business pillars (X2) and financial pillars (X3) while the remaining 38.9% is explained by other factors or variables outside the model. The result of simultaneous F test counted at 29,941 with a significantly smaller than 0.05 so that there was a positive influence between institutional pillar variables, business pillars and financial pillars on cooperative performance in Medan City.